PERHITUNGAN DAYA DUKUNG PONDASI TIANG PANCANG BERDASARKAN DATA SONDIR (CONE PENETRATION TEST) MENGGUNAKAN METODE (SHERTMANN & NOTTINGHAM,GUY SANGLERAT) - Br.Sormin, Elisabet; Simorangkir , Simon Petrus (Universitas Asahan, 2025)
In the construction world, foundation work is one of the most important elements of a building structure. Foundations serve to safely and stably transfer the load from the superstructure to the ground. In this study to calculate the bearing capacity of pile foundations using the Schmertmann & Nottingham method and the Guy Sanglerat method using sondir data obtained based on the sondir data of Soil Bearing Capacity using the Schmertmann & Nottingham method on sondir 2, namely qu = 176.8 qa = 58.93, Single Pile Foundation Bearing Capacity using the Schmertmann & Nottingham method on sondir 2, namely Qa = 51.581, Guy Sanglerat Method, namely Qa = 26.821, and the bearing capacity value of the 4-pile foundation group of the Schmertmann & Nottingham method Qa = 123.794, Guy Sanglerat Method Qa = 82.994, the bearing capacity value of the 5-pile foundation group of the Schmertmann & Nottingham method, namely Qa = 129.984, Guy Sanglerat Method Qa = 87.143. In this study, the Schmertmann & Nottingham method produced the highest bearing capacity value at sondir 2 compared to the guy sanglerat method